As proposições de Antonio de Saldanha da Gama para a melhoria do tráfico de escravos, por questões humanitárias e econômicas, Rio de Janeiro, 1810 - Viotti, Ana Carolina de Carvalho [UNESP] (FapUNIFESP (SciELO), 2016)
In 1808, Dom João VI issued an edict which regulated the shipping and treatment of slaves on the transatlantic crossing from Africa. Two years later, Antonio de Saldanha da Gama, a member of the Treasury Council, drafted a letter discussing some points of the resolution. This key figure in the Portuguese administration of Brazil argued that his respectful considerations concerning the determinations of His Royal Highness were designed to improve them for humanitarian and economic reasons. Safeguarded in the archives of Arquivo Histórico Ultramarino, this letter is transcribed, annotated, and contextualized here, supplying an interesting perspective on the prevailing concerns and justifications about the trafficking of African slaves to Brazil.
Antonio de Saldanha da Gama’s proposals to improve the slave trade for humanitarian and economic reasons, Rio de Janeiro, 1810
Keywords: Diseases; Hygiene; Legislation; Prescriptions; Slave trade